Differences in disease severity and in-hospital mortality in patients hospitalised for pneumonia with and without intellectual disabilities: A matched-pair retrospective cohort study using nationwide in-patient database. Issue 1 (2nd January 2022) - Hirose, Naoki; Morita, Kojiro; Jo, Taisuke; Hagiwara, Yasuhiro; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
ABSTRACT: Background: We examined the association between intellectual disabilities (ID) and pneumonia severity at admission. Methods: We extracted patients admitted to hospital for pneumonia from July 2010 to March 2018 using the Diagnosis Procedure Combination database. We measured pneumonia severity using the A-DROP system. After 1:4 cohort matching between patients with and without ID, we conducted conditional logistic regression and mediation analyses. Results: Of 1, 141, 158 patients, 531 had ID, and they had more severe pneumonia at admission (24.5% vs. 9.5%; P  < 0.001). ID was significantly associated with severe pneumonia at admission (OR = 3.50; 95% CI: 2.68–4.58) and activities of daily living (ADL) mediated 73.8% (95% CI: 50.9%–105.0%) of the total association. Conclusions: Social barriers caused by reduced ADL may prevent patients with ID from accessing health care before their pneumonia becomes severe. Removing these barriers may decrease mortality from pneumonia among patients with ID by improving health care access.